Microwave hydrothermal synthesis of hierarchical Ce-doped MoSe2@CNTs as an efficient non-precious catalyst for hydrogen evolution in both acidic and alkaline media. (February 2022) - Yao, Yanhua; Liu, Changhai; Luo, Linlin; Ji, Dingwei; Wang, Wenchang; Chen, Zhidong
Highlights: The microwave-assisted hydrothermal synthesis is adopted to prepare hierarchical Ce-doped MoSe2 @CNTs. The multifolded MoSe2 structure on multi-walled carbon nanotubes (MWCNTs) can effectively increase the active sites for electrocatalytic reaction. The optimal Ce-MoSe2 @CNTs catalyst shows high performance for HER in both acidic and alkaline conditions. The enhancement of HER activity can be attributed to the enhanced conductivity of CNTs and the reduced strength of Mo-H bonding. Abstract: To enhance the intrinsic activity and the density of active sites of the electrocatalyst for the hydrogen evolution reaction (HER), the microwave-assisted synthesis is adopted to prepare hierarchical Ce-doped MoSe2 @CNTs as highly-efficient catalysts for HER in both acidic and alkaline conditions. The well-defined hierarchical nanostructure of Ce-doped MoSe2 on multiple carbon nanotubes (MWCNTs) with few layers of MoSe2 nanostructure. The Ce-MoSe2 @CNTs sample with an optimal proportion of Ce:Mo (1:5) exhibits outstanding activity and long-term stability in both acidic and alkaline electrolyte. It shows an overpotential of 108 and 166 mV at 10 mA cm −2 in acidic and alkaline electrolyte, respectively. This study offers a prospective opportunity to design and fabricate the highly-effective catalysts coupling with multiple synergistic effect for efficient electrocatalysts. Graphical abstract: Image, graphical abstract